The use of mobile technology in higher education: implications for students and instructors - Thaanyane, Mamosa; Jita, Thuthukile (Edelweiss Applied Science and Technology, 2024)
Mobile learning has become a prominent topic in educational settings today due to its significant developments in information and communication technology (ICT). This flexibility not only benefits student-teachers who can learn at their own pace and convenience but also empowers instructors to engage with their student-teachers more dynamically. Literature indicates that mobile learning encourages collaboration and active participation, fostering critical thinking skills and creating a more engaging learning experience. Despite the many advantages of integrating technology into the classroom, research indicates that most faculties higher education are resistant to incorporating technology into their activities since there are no institutional norms. The study aims at evaluating the use of mobile learning in higher education in Lesotho and the implications it has on both instructors and student-teachers when using mobile learning. The study adopted a systematic literature review to review the available research using an integrative method of studies conducted on mobile learning in higher education between 2013 and 2023. The study found that some instructors ban the use of mobile devices because they distract from teaching and learning. In addition, not all devices can handle the demands of remote learning. Student-teachers believe that mobile technology enhances communication with peers and instructors. Among other factors, limited Internet connectivity and funding are the most common inhibiting factors for instructors to adopt technology into the teaching and learning process. Other inhibiting factors are the high costs of mobile data access and smart mobile devices. The study recommends that ICT policy must be in place to manage and control mobile learning for effective adoption.